Implementasi Gerakan Literasi Sekolah Tahap Pembiasaan dalam Meningkatkan Minat Baca Siswa Kelas 4A SDN Kaliasin VII Surabaya - Hurin Nabila; Muhammad Thamrin Hidayat; Syamsul Ghufron; Rudi Umar Susanto (Journal on Education, 2023)
This study aims to describe the implementation of the habituation stage of the school literacy movement, the inhibiting factors, supporting factors, the positive impact of the habituation stage of the school literacy movement in increasing students' reading interest in grade 4A SDN Kalisian VII Surabaya. This type of research is qualitative research with data collection techniques, namely interviews, observation and documentation. The data analysis technique used is data reduction, data presentation and conclusions or data verification. The results of the research at SDN Kaliasin VII Surabaya, namely the implementation of the habituation stage of the school literacy movement is carried out every day before learning begins. The inhibiting factors for the implementation of literacy activities at the habituation stage include: (1) Limitations on updating reading books, (2) students are not yet fluent in reading, (3) There is no reading area in the school environment. The supporting factors for the implementation of literacy activities at the habituation stage are there is a literacy team, the role of the teacher or homeroom teacher, there is a display board as a place for student appreciation, the library and classrooms are equipped with technology and a class reading corner as well as a library of various sources of reading books. The positive impacts of implementing literacy activities at the habituation stage include: (1) making students dare to appear in front of the class, (2) increasing visits to the library and using the library as a place to do school work, (3) student achievement in participating in competitions based on literacy and outside literacy.